Middelburg, Abdijplein Archeologische begeleiding Middelburg- Abdij, Middelwwuse muur en dierresten van het "Vuile Pleintje" - Spitzers, T. (DANS Data Stations, 2024)
Keywords: middelburg

Willem II of Floris de Voogd? Vragen rond een grafmonument en een skelet in de Koorkerk te Middelburg - Henderikx, Peter A. (Bijdragen en mededelingen betreffende de geschiedenis der Nederlanden, 2015)
William II or Florence the Guardian?: Questions about a Tomb and a Skeleton in the Abbey Church at Middelburg Both William II, Count of Holland and Zeeland and King of the Holy Roman Empire (†1256, re-interred 1282) and his brother Florence the Guardian (†1258) are buried in the Norbertine abbey church in Middelburg. In 1817 a skeleton was found in a bricked up niche, along with the remains of a tombstone on which was carved a knightly figure whose shield bears the coat of arms of Holland. Based on the results of an examination of the bones by George J.R. Maat and his team (Leiden University Medical Centre), Henderikx takes it that the skeleton could be either that of the King of the Holy Roman Empire or of Florence the Guardian. Considering that the skeleton, burial space and tombstone formed a coherent whole, and the high-relief on the tombstone almost certainly does not refer to the King of Rome but to his brother, Henderikx concludes that the skeleton must be the earthly remains of Florence the Guardian.
Keywords: middelburg

De graven en grafmonumenten van graaf/rooms-koning Willem II en Floris de Voogd in het koor van de abdijkerk Middelburg - Henderikx, Peter A. (Archief: mededelingen van het Koninklijk Zeeuwsch Genootschap der Wetenschappen, 2014)
Keywords: middelburg

Egidius (Gillis) van Leeuw, premonstratenzer kruisprediker, kruisvaarder naar Damietta en abt van Middelburg en Vicoigne († 1236) - Van Moolenbroek, Jaap (Analecta Praemonstratensia, 2012)
Keywords: middelburg; vicoigne

De Abdij van Middelburg - Dekker, Janna Catharina; Zonnevylle-Heyning, C.E. (Uitgeverij Matrijs, 2006)
Keywords: middelburg

Een archeologisch onderzoek in de vroegmiddeleeuwse ringwalburg op het Abdijplein te Midddelburg, gemeente Middelburg (Z.) - Ufkes, A. (DANS Data Station Archaeology, 2006)
Keywords: middelburg

Dierlijke resten uit de abdij van Middelburg - Beerenhout, B.; Esser, E. (DANS Data Station Archaeology, 2005)
Keywords: middelburg

Het Abdijcomplex te Middelburg architectonisch bedrog? - Zaceagnini-Visser, Rosa (Bulletin van de Koninklijke Nederlandse Oudheidkundige Bond, 2003)
Keywords: middelburg